2017
DOI: 10.4253/wjge.v9.i10.529
|View full text |Cite
|
Sign up to set email alerts
|

Cap polyposis refractory to Helicobacter pylori eradication treated with endoscopic submucosal dissection

Abstract: Cap polyposis is a rare intestinal disorder. Characteristic endoscopic findings are multiple inflammatory polypoid lesions covered by caps of fibrous purulent exudate. Although a specific treatment has not been established, some studies have suggested that eradication therapy for Helicobacter pylori (H. pylori) is effective. We report a case of a 20-year-old man with cap polyposis presenting with hematochezia. Colonoscopy showed the erythematous polyps with white caps from the sigmoid colon to rectum. Histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…The lesion was located in the gastric antrum, and fibromuscular obliteration of the muscularis propria caused an elevated lesion. Fibromuscular obliteration of the muscularis propria is reported in conditions such as rectal mucosal prolapse syndrome and occurs when smooth muscle bundles extend from the muscularis mucosa into the lamina propria [ 21 ]. In our case, immunohistochemical staining indicated fibromuscular obliteration around the pyloric glands in the background mucosa surrounding the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion was located in the gastric antrum, and fibromuscular obliteration of the muscularis propria caused an elevated lesion. Fibromuscular obliteration of the muscularis propria is reported in conditions such as rectal mucosal prolapse syndrome and occurs when smooth muscle bundles extend from the muscularis mucosa into the lamina propria [ 21 ]. In our case, immunohistochemical staining indicated fibromuscular obliteration around the pyloric glands in the background mucosa surrounding the lesion.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 10 , 16 Because there have been no reports of malignant transformation in cap polyposis, surgical resection may be unnecessary. As a less invasive alternative, Murata et al 17 suggested endoscopic management with ESD en bloc excision. In the present case, the extent of submucosal fibrosis and the circumferential nature and localization of the lesions would have made ESD very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is less invasive, EMR should be recommended for most patients with rectosigmoid involvement, especially for those with few polyps. Endoscopic submucosal dissection (ESD) was also reported to be successful in an intractable cap polyposis with rectosigmoid involvement [ 5 ]. ESD might be a treatment option for cases that are refractory to conservative treatments.…”
Section: Discussionmentioning
confidence: 99%